(untitled) (Global Journal of Medical Research, 2014)
The so-called point Gräfenberg popularly known as "G-spot" corresponds to a vaginal area 1-2 cm wide, behind the pubis in intimate relationship with the anterior vaginal wall and around the urethra (complex clitoral) that when the woman is aroused becomes more sensitive than the rest of the vagina. Some women report that it is an erogenous area which, once stimulated, can lead to strong sexual arousal, intense orgasms and female ejaculation. Although the G-spot has been studied since the 40s, disagreement persists regarding the translation, localization and its existence as a distinct structure. Objective: Understand the operation and establish the anatomical points where the point G from embryology to adulthood. Methodology: A literature search in the electronic databases PubMed, Ovid, Elsevier, Interscience, EBSCO, Scopus, SciELO was performed. Results: descriptive articles and observational studies were reviewed which showed a significant number of patients. Conclusion: Sexual pleasure is a right we all have, and women must find a way to feel or experience orgasm as a possible experience of their sexuality, which necessitates effective stimulation.